Does fintech contribute to systemic risk? Evidence from the US and Europe - Lavinia Franco; Ana Laura García; Vigor Husetović; Jessica Lassiter (Asian Development Bank Institute (ADBI), 2020)
Fintech has increasingly become part of the global economy with the evolution of technology, increasing investments in fintech firms, and greater integration between traditional incumbent financial firms and fintech. Since the 2007-2009 financial crisis, research has also paid more attention to systemic risk and the impact of financial institutions on systemic risk. As fintech grows, so too should the concern about its possible impact on systemic risk. This paper analyzes two indices of public fintech firms (one for the United States and another for Europe) by computing the ΔCoVaR of the fintech firms against the financial system to measure their impact on systemic risk. Our results show that at this time fintech firms do not contribute greatly to systemic risk.
Keywords: G01; G20; G28; O30; 330; fintech; systemic risk; financial crisis; regulation